Assessing the toxicity of peracetic acid to early Atlantic salmon Salmo salar life‐stages. (7th July 2022) - Redman, Natalie; Straus, David L.; Annis, Eric R.; Murray, Megan; Good, Christopher
Abstract: Bacterial and fungal pathogens in recirculating aquaculture and egg incubation systems can cause elevated mortality and decreased production. Peracetic acid (PAA) is a relatively low‐cost, safe, and effective disinfectant; however, its toxicity to early life stages of the Atlantic salmon ( Salmo salar ) has not been assessed. The 24‐h LC50 value of PAA was determined for three early life stages of Atlantic salmon: eyed eggs, fry ( 0.17 g), and fingerlings ( 16.3 g). LC50 values were calculated using the Trimmed Spearman‐Karber (TSK) method and Toxicity Relationship Analysis Program (TRAP). TRAP LC50 values for eyed eggs treated for 5 and 10 min were 781.5 and 485.0 mg/L PAA, respectively, while TSK LC50 values for eyed eggs treated for 5 and 10 min were 771.1 and 462.1 mg/L PAA, respectively. TRAP LC50 values for fry and fingerlings were 4.0 and 5.3 mg/L PAA, respectively, while TSK LC50 values for fry and fingerling were 4.1 and 5.3 mg/L PAA, respectively. The no observed effect concentration (NOEC) values for eyed eggs treated for 5 and 10 min were 500 and 300 mg/L PAA, respectively. These LC50 and NOEC values provide guidance for developing safe PAA treatment protocols Atlantic salmon eggs, fry, and/or fingerlings.